133k views
4 votes
Expand and then and then collect the following expression 3(a+2)+6(a+3)

User Jimbali
by
4.9k points

2 Answers

5 votes

Answer:

9a+24

Explanation:

3a+6+6a+18

Simplify:

9a+24

User Kacperito
by
5.4k points
0 votes

Answer:

9a + 27

Explanation:

=> 3(a+3) + 6(a+3)

Expand the brackets

=> 3a+9 + 6a+18

Combining like terms

=> 3a+6a+9+18

=> 9a + 27

User Muzzamo
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.